Handbook of Stemmatology History, Methodology, Digital Approaches - Roelli, Philipp (De Gruyter Reference, 2020)
Stemmatology studies aspects of textual criticism that use genealogical methods. This handbook is the first to cover the entire field, encompassing both theoretical and practical aspects, ranging from traditional to digital methods. Authors from all the disciplines involved examine topics such as the material aspects of text traditions, methods of traditional textual criticism and their genesis, and modern digital approaches used in the field.